KERJASAMA INDONESIA DAN ISLANDIA DALAM PENGEMBANGAN ENERGI PANAS BUMI (GEOTHERMAL) TAHUN 2009-2014 - Mutiara Sari; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research is the study of diplomacy and strategy analyzes about Indonesia and Iceland on cooperation in geothermal energy development in 2009-2014. The purpose of this research is Indonesia as fossil fuel users are faced with the depletion of oil reserves of Indonesia due to increasing needs of Indonesia society.This makes the Indonesian government seek and develop new energy sources such us geothermal energy, so cooperation with Iceland which has succesfully in developed geothermal energy to tackle national energy security.This research used qualitative methods which is done by explaining the case based on existing facts. The techniques used to collects data to study the case to library research in the form of journals, books, official documents, report, magazine, paper, and website. The theoretical framework applied in this research are neorealism perspective, national interest concept, nation-state analysis level and decision making theory.The result of this describes the forms of cooperation between Indonesia and Iceland in geothermal energy development is to include the exploration, exploitation, the use of geothermal energy and geothermal dispatch experts to Indonesia to study Iceland regarding geothermal energy development and investments.Keywords :Cooperation, Energy, Geothermal, Development, Indonesia, Iceland